Quality evaluation of bread produced from blends of wheat and acha flours complemented with Defatted Bambara Groundnut Flour - Ayo, J.A; Esan, Y.O; Okpasu, A; Gbuusu, B; Mohammed, Z.A; Tyvakase, T (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2024)
The study investigated the quality of bread produced from blends of wheat and acha flours complemented with defatted bambara groundnut flour (DBGNF). Chemical composition, physicochemical properties and sensory evaluation were carried out on the breads while the flour blends were assessed for functional properties. DBGNF was incorporated into wheat-acha flour blends at 5, 10, 15, 20 and 25% respectively with 100% wheat and acha flour breads as controls. Moisture, crude protein, crude fibre, and ash content of the breads increased from 24.17 to 27.20, 11.69 to 13.12, 0.26 to 0.77 and 1.06 to 1.19% respectively while crude fat and carbohydrate content decreased from 8.67 to 7.66% and 54.20 to 50.20% with increased level of DBGNF. Phosphorus and iron increased from 162.2 to 229.82 and 0.87 to 1.24 mg/100g whereas zinc decreased from 0.52 to 0.09 mg/100g with addition of DBGNF. Phenol, flavonoid and carotenoid contents decreased from 45.50 to 41.96, 28.74 to 19.68 and 0.20 to 0.02 mg/100g respectively. The foaming, emulsifying, swelling, water and oil absorption capacity of the flour blends increased while bulk density decreased with addition. Vitamins B1 and B2 content decreased with increasing DBGNF inclusion. The loaf weight increased while loaf volume and loaf volume index decreased with increasing level of DBGNF. Bread sample containing 10% DBGNF was not significantly different from the 100% wheat bread in terms of sensory attributes. The research showed that the addition of DBGNF improved the functional quality and nutrient composition of the composite bread and the sample containing 10% DBGNF was the most preferred.